From self-awareness to self-actualization: empowering sepsis survivors to a meaningful and enduring recovery - Anderson, Brian J.; Mikkelsen, Mark E. (Journal of Thoracic Disease, 2016)
The rising incidence of sepsis and improvements in critical care medicine have led to a growing number of sepsis survivors (1). Unfortunately, many intensive care unit (ICU) survivors suffer impairments in cognitive function, physical function and mental health (2-5).